Chagas disease - risk assessment by an environmental approach in northern Argentina - Chuit, Roberto (2011)
Chagas' disease vector control has been based almost exclusively on the use of insecticides, A complementary control strategy highlighting environmental management has been developed based on analysis of field data from an endemic community in Santiago del Estero, Argentina, High and low risk factors for human Trypanosorna cruzi infection were identified using the Grade of Membership (GOM) model, The characterization of especially low and high-risk habitats given a highly heterogeneous endemic setting where several environmental and host-related indicators were possible determinants of seropositivity rate. Number of peridomestic structures, and the household number of dogs or cats were identified and the benefit of such an approach is that its control can be carried out at the household level, The seropositivity rate among children ages 5-14 in high-risk habitats was 36.4%, whereas in low risk habitat it was 7.7%, This difference is striking for an undemic community with no prior experience of Chagas' disease control interventions.